Production performance and business analysis of clown loach Chromobotia macracanthus (Bleeker 1852) in recirculating systems with different stocking densities and water discharge - Riska Puluhulawa; Tatag Budiardi; Iis Diatin; Irzal Effendi (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2021)
Efforts to improve the production performance of clown loach in recirculate aquaculture system can be done by increasing stocking density and water discharge. This study aimed to analyze the effect of increasing stocking density and water discharge on production performance, stress response and water quality in order to obtain the best stocking density and water discharge to obtain maximum profit in a short time. A factorial completely randomized design with two factors, i.e. the stocking density of 1, 2, and 3 fish L-1 and the water discharge of 0,05; 0,10; 0,15 L s-1 was performed. The volume of water used in each aquarium was 48 L and using a ½ inch faucet stop to regulate the water discharge from the inlet pipe. Clown fish fed Tubifex sp. with a feeding frequency of two times a day according to the treatment for 60 days. The result indicates that there was no interaction between the two factors on production performance, payback period, and R/C ratio. Stocking density has a significant effect on specific growth rate, absolute growth rate of individual weight, feeding consumption rate and R/C ratio of clown loach. Stocking density and water discharge had an interaction on the visual color of pectoral and caudal fins of clown loach. Different stocking densities with the combination of water discharge in this study resulted that the water quality were within tolerable range for clown loach so that they did not experience stress, as well as high production and business performance. It is recommended to intensify clown loach with a stocking density of 3 fish L-1 and 0,15 L s-1‑ of water discharge. Abstrak Upaya intensifikasi ikan botia melalui peningkatan padat tebar dilakukan untuk meningkatkan kinerja produksinya. Penelitian ini dilakukan untuk menganalisis pengaruh peningkatan padat tebar dan debit air terhadap kinerja produksi, respons stres dan kualitas air, guna mendapatkan padat tebar dan debit air terbaik sehingga diperoleh keuntungan maksimal dalam waktu yang singkat. Penelitian ini menggunakan rancangan acak lengkap faktorial dengan dua faktor, yaitu padat tebar 1, 2, dan 3 ekor L-1 serta debit air 005; 0,10; dan 0,15 L s-1. Volume air yang digunakan pada masing-masing akuarium sebanyak 48 L dan menggunakan stop keran ½ inci untuk mengatur debit air pada pipa inlet. Pakan Tubifex sp. diberikan sebanyak dua kali sehari sesuai dengan perlakuan selama pemeliharaan 60 hari. Hasil penelitian menunjukkan bahwa tidak terdapat interaksi antara faktor perlakuan padat tebar dan debit air terhadap seluruh parameter kinerja produksi, payback period, dan R/C ratio. Faktor perlakuan padat tebar berpengaruh nyata terhadap laju pertumbuhan bobot spesifik, laju pertumbuhan mutlak bobot individu, nisbah konversi pakan dan R/C ratio. Padat tebar dan debit memiliki interaksi terhadap warna visual sirip dada dan sirip ekor ikan botia. Kombinasi padat tebar dan debit air berbeda dalam penelitian ini menghasilkan kualitas air yang dapat ditoleransi ikan botia sehingga tidak mengalami stres dan meningkatkan kinerja produksi serta analisis usaha. Berdasarkan penelitian, direkomendasikan untuk melakukan upaya intensifikasi ikan botia dengan padat tebar 3 ekor L-1 dan debit air 0,15 L s-1.